COVID‐19 and kidney transplantation: Results from the TANGO International Transplant Consortium. Issue 11 (4th August 2020) - Cravedi, Paolo; Mothi, Suraj S.; Azzi, Yorg; Haverly, Meredith; Farouk, Samira S.; Pérez‐Sáez, María J.; Redondo‐Pachón, Maria D.; Murphy, Barbara; Florman, Sander; Cyrino, Laura G.; Grafals, Monica; Venkataraman, Sandheep; et al.
Abstract : Kidney transplant recipients may be at a high risk of developing critical coronavirus disease 2019 (COVID‐19) illness due to chronic immunosuppression and comorbidities. We identified hospitalized adult kidney transplant recipients at 12 transplant centers in the United States, Italy, and Spain who tested positive for COVID‐19. Clinical presentation, laboratory values, immunosuppression, and treatment strategies were reviewed, and predictors of poor clinical outcomes were determined through multivariable analyses. Among 9845 kidney transplant recipients across centers, 144 were hospitalized due to COVID‐19 during the 9‐week study period. Of the 144 patients, 66% were male with a mean age of 60 (±12) years, and 40% were Hispanic and 25% were African American. Prevalent comorbidities included hypertension (95%), diabetes (52%), obesity (49%), and heart (28%) and lung (19%) disease. Therapeutic management included antimetabolite withdrawal (68%), calcineurin inhibitor withdrawal (23%), hydroxychloroquine (71%), antibiotics (74%), tocilizumab (13%), and antivirals (14%). During a median follow‐up period of 52 days (IQR: 16‐66 days), acute kidney injury occurred in 52% cases, with respiratory failure requiring intubation in 29%, and the mortality rate was 32%. The 46 patients who died were older, had lower lymphocyte counts and estimated glomerular filtration rate levels, and had higher serum lactate dehydrogenase, procalcitonin, and interleukin‐6 levels. In sum, hospitalized kidney transplant recipients with COVID‐19 have higher rates of acute kidney injury and mortality. Abstract : In this multinational cohort of 144 kidney transplanted patients from 11 transplant centers in the US and Europe who were hospitalized for COVID‐19, acute kidney injury occurred in 52% and respiratory failure requiring intubation occurred in 29%, with an overall mortality of 32%.